Before We Dreamt of Ourselves as Electric Beings. Sci-fi and Dystopia at the End of Francoism - Regueira, Mario (Madrygal. Revista de Estudios Gallegos, 2023)
The relationship of Galician culture with fields such as Science Fiction has specific features. In the history of Galician literature, the publication of Soños eléctricos by Ramón Caride in 1992 is referred as the first literary approach to this subgenre. However, we can find other precedents connected to Science Fiction in the years between the end of the Francoism and the launch of that emblematic book. This article analyses the impact of those literary works which were written before that date and independently from the main literary lines explored in the Galician published sector during the period of wide development in the endthe 20th Century. It pays special attention to those factorswhich made of them literary works located in the culturaland historical margins, due to the fact of being previousor antagonist to the “cultura da normalización”. In addition,following the idea that futuristic speculations havean explicit or implicit political dimension, this articleanalyses how this dimension applies to theses study cases.In order to do so, this article examines their relationwith science and technology, how they present social organization, the possibility of a postcolonial reading and,more specifically, representations of gender and sexualityby applying the approach provided by Queer Studies toidentify alternatives and persistences of heteronormativeculture.
Keywords: Science Fiction; Post-Francoism; Galician Literature; Queer Studies; Distopia